Ambient Lighting Integrated Assistance System - Pedro Miguel de Almeida (2015)
This work aims to provide a personalized wireless ambient lighting for assistance environments. The main idea is to use an ambient lighting as a communication channel and as health support system. Knowledge from circadian rhythm and colored lighting will be used to provide an improved self-healing environment. Other functionalities include the reaction to external events captured by sensors, changing the lighting status in order to serve as a visual communication and notification channel, readily understood. The development of such a tool is composed by the development of 4 essential sub-parts: 1) Android app for the user defined settings such as types of external events and their visual notifications, as well as the activation of predefined lighting configurations; 2) Web application for programming complex user defined lighting scenes and configurations; 3) Web server that provides the services necessary for the user, getting and storing user settings and lighting status as well as command light bulbs actions from external events or circadian rhythm updates, 4) Database where all the user defined settings and lighting status are stored.In the future, the tool can also allow to put in practice and test existing theories and studies about lighting, colors and circadian rhythm effects on humans.